Penerapan Terapi Madu Murni untuk Menurunkan Frekuensi Batuk pada Anak dengan Bronkopneumonia di Bangsal Melati RSUD Sleman - Nur Rohmah, Popong; Dias Utami, Khristina (Jurnal Indonesia Sehat, 2025)
Background: Bronchopneumonia is a major cause of morbidity in children, characterized by cough, dyspnea, and increased sputum production. Persistent cough may lead to ineffective airway clearance, requiring supportive therapy in addition to medical treatment. Pure honey is a complementary therapy with anti-inflammatory and antimicrobial properties that can soothe the respiratory tract and reduce coughing. Objective: This case study aimed to apply pure honey therapy to reduce cough frequency in children with bronchopneumonia in the Melati Ward of RSUD Sleman. Methods: A case study design was conducted on a 2-year-old child diagnosed with bronchopneumonia. Data were collected through interviews with parents, clinical observation, respiratory physical examination, and medical record review. Instruments included a pediatric nursing assessment form, cough frequency observation sheet, and a stethoscope for auscultation. Nursing care documentation was based on SDKI, SLKI, and SIKI. The intervention consisted of administering 10 cc of pure honey mixed with warm water twice daily for three days. Data were analyzed descriptively by comparing cough frequency before and after the intervention and evaluating daily clinical changes. Results: After three days of pure honey therapy, cough frequency decreased from frequent to occasional. Clinical improvement was also observed, including reduced adventitious breath sounds, decreased sputum production, and improved airway clearance. Conclusion: Pure honey therapy is effective in reducing cough frequency in children with bronchopneumonia and may be used as a complementary intervention in pediatric nursing care.